WASTE MANAGEMENT PROBLEMS IN THE «FAR EASTERN» AND «ARCTIC» HECTARE DEVELOPMENT - MASHKOVA Tatyana Yuryevna (Правовое государство: теория и практика, 2023)
Currently, one of the urgent socioeconomic and demographic tasks of the Russian Federation is the implementation of a longterm program for the resettlement of citizens to remote Far Eastern and Arctic territories of the country. Nevertheless, the almost six-year period of the special «Far Eastern» legislative act has not shown good results. One of the numerous reasons for this, according to the author, is the insufficient accounting of lands contaminated by production and consumption waste in the Federal Information System «nadalniyvostok.rf» (hereinafter – FIS), in which land plots for citizens – potential owners of Far Eastern hectares and Arctic hectares – are presented as suitable for development. Purpose: to analyze legal and socio-environmental problems related to the development of the «Far Eastern hectare» and «Arctic hectare» programs, land pollution by industrial and municipal (or household) waste, «accumulated environmental harm» of the Arctic zone of Russia. Methods: comparison, description, formal and dialectical logic, legal-dogmatic and interpretation of legal norms. Results: the study reveals the shortcomings of organizational and licensing activities of municipal and regional authorities of the Far Eastern and Arctic regions, as well as the Federal Registration Service (Rosreestr) bodies related to the implementation of the «Far Eastern hectare» and «Arctic hectare» programs. On the one hand, in order to eliminate the identified problems, it is necessary to clarify and adjust the location of the land plots designated in the FIS for the realization of citizens’ rights to the Far East hectare and Arctic hectare. On the other hand, the study highlights the need to better identify the areas of accumulated environmental damage and production and consumption waste disposal, as well as to adjust the regional legislation to avoid the allocation to the «Far East Hectare» program of territories previously used for the production and consumption waste disposal.